Screening of polyhydroxyalkanoates producing bacteria isolated from marine ecosystems - Baptista, Silvia de Almeida (2015)
Polyhydroxyalkanoates (PHAs) are biodegradable polyesters and environmentally friendly thermoplastics, which are accumulated as carbon and energy storage materials in various bacteria in limited growth conditions with excess carbon sources. In this study, bacteria were isolated from samples taken from various marine ecosystems in the Archipelago of Madeira in the Atlantic Ocean, and screened for their ability to accumulate polyhydroxyalkanoates. These samples were taken from the seabed at depths of 30 and 1,700 meters to obtain a larger diversity of microorganisms and therefore, in an attempt to obtain new structures of PHAs. Strains were directly isolated from 612 mother plates where marine samples had been initially plated. A total of 724 isolates from mother plates were obtained, of which 174 were found PHA-positive using Nile red viable-colony screening. All synthesized intracellular inclusions during growth on starch carbon source. Twenty-five bacterial isolates in 25 mL-scale cultivation were proven promising for PHA production with PHA storage maximum 17.71 % for MD12-107 and 9.30 % for MD12-581 strain. The inclusions were predominantly identified as poly-β-hydroxybutyrate (PHB) using gas chromatography. Strains MD12-107 and MD12-581 were tested in 100 mL-scale and bioreactor cultivation. The best results were achieved with strain MD12-581 accumulated PHA storage 15.40 % in less than 6.5 hours with 5.5 g/L of cell dry weight and a specific growth rate was 0.24 h-1 when grown in medium containing 40 g/L of starch, 8 g/L of yeast extract and 4 g/L of peptone during batch cultivation.